Família, Rua e Afeto: etnografia dos vínculos familiares, sociais e afetivos de homens e mulheres em situação de rua - Silva, Tiago Lemões da (2012)
By an anthropological approach, this study discusses the relations maintained, created and updated by both men and women on the streets in the center of Pelotas/RS. To discuss these relationships, the research is structured from a threefold approach: the continuity of family relationships in the context of the streets; strategies for building and maintaining links with different characters in the public space of sociability; and codes that guide the establishment of relationships between pairs on the streets. From the ethnographic method,the research finds: family relationships as part of a broader relational circuit which includes street and the characters with which they interact in this space; discusses also the mechanisms of construction and perpetuation of bonds with different social segments in the streets context, considering the dynamics of material and symbolic exchanges fought in these relationships. Finally, analyzes of social codes that shape the formation of groups in the streets and the establishment of diffuse and enduring links between those involved